Fenomena Linguistik dalam Realitas Sosial Budaya di Era Covid-19 - Eva Fachriyah; Endang Tri Santi; Ratu Dea Mada Badriyah (Universitas Serang Raya, 2022)
The Corona Virus, also known as COVID-19 (Corona Virus Diseases 2019), is a very common infection these days. Currently, all fields are related to COVID-19, including the field of language that highlights the use of terms used in everyday communication, in prevention and treatment efforts, and the tools used that are widely emerging. Some of these terms, some of which have been around for a long time but whose use is becoming popular at this time, are also new terms that emerged during the Coronavirus outbreak. The emergence of these linguistic terms shows that language is productive and dynamic so that its development is appropriate and in line with the situation and conditions that occur. The linguistic term related to COVID-19 appears as a description of what is happening and an expression of an effort to prevent the spread of the Coronavirus. However, behind the function of language as a very basic communication tool, namely the description of something or what is happening, there are also language polemics such as negligence in the use of terms and cultural puns that can be interpreted negatively by the interlocutor. This research is qualitative descriptive research using the discourse analysis method. The data obtained are interpreted by involving language theory. From the results of the analysis, at least many things related to language that have emerged related to COVID-19 include word forms, phrases, acronyms, patient status domains, actions, equipment, and regions. In addition, several polemics have also emerged, such as the categorization of linguistic symbols, the omission of symbols, and cultural play.